2021
DOI: 10.18231/j.jmra.2021.014
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination drive: Impact on the acceptance of vaccine among the general population of India

Abstract: The acceptance of any vaccine relies on the belief and perception towards it. After a wait of almost 10 months, the COVID-19 vaccine is ready with the first phase in progress in India. The aim of this study is to assess the impact on the acceptance intentions of COVID-19 vaccine among the general population of India after the vaccine is inoculated to health care workers in the first phase. An empirical study was conducted by analyzing the data collected by a self-administered questionnaire. The various variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…According to a cross-sectional study among the general public of south India reported an acceptance rate of 69% among its population. 15 In our study finding, the results indicate higher acceptance rate of 55% in males followed by 45% in females. Higher rate of acceptance was found among males than females.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…According to a cross-sectional study among the general public of south India reported an acceptance rate of 69% among its population. 15 In our study finding, the results indicate higher acceptance rate of 55% in males followed by 45% in females. Higher rate of acceptance was found among males than females.…”
Section: Resultssupporting
confidence: 51%
“…According to the study conducted by Bhargava et al it was found that participants with postgraduation educational status showed higher acceptance rate of 59.7%, whereas undergraduate showed acceptance of 57.7%. 15 According to the results from our study highest rate of acceptance was found to be in postgraduates (35%) and undergraduate (31%). The responders with 29% of vaccine acceptance were found to be in people with secondary education (9-12 std).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Looking at the statistics, it is revealed that approximately up to 13 to 17% of people aged more than 60 years were infected in the first wave and almost the same percentage in the second wave ( 28 , 29 ), and this group was also among the first categories in which the vaccination was started and by the time of the second wave many of them were due for the second dose of their vaccine which can lead to seropositivity for anti-spike IgM and IgG antibodies. Furthermore, for the elderly who were positive previously or had their family members positive, it is expected to have more acceptive behavior and practice for the vaccine, so the presence of anti-nucleocapsid IgG antibody, as already stated, may be a sign of previous recent past infection in them ( 30 33 ). Those with comorbidity and with female gender also had a higher seroprevalence of the three antibodies as compared to their counterparts; same factors as stated in the elderly age can explain the scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that the acceptance rate varied from 41 to 81.3% among population groups. 11 12 A global survey analyzing the acceptance rate of COVID-19 vaccine among 10 low and middle income countries have shown that the vaccine acceptance rate was 80.3%. 13 However, as of August 2021, only 8.9% of the total population have been vaccinated in India.…”
Section: Rate Of Acceptance Of Covid-19 Vaccinationmentioning
confidence: 99%